Phenomenon-Based Learning on Critical Thinking and Environmental Literacy of Students at Wat Wan Uthit School (Sirikamolchamratbumrung), Ang Thong Province - Wetchawong, Patchapa; Mahavijit, Pongsatorn; Srisa-ard, Sirirat (MCU Haripunchai Review, 2026)
This research aimed to 1) develop phenomenon-based learning activities for the Science Project subject for Matthayom 2 students, and 2) study the effects of phenomenon-based learning activities on students’ critical thinking and environmental literacy at Wat Wan Uthit School (Sirikamolchamratbumrung). The study was applied research conducted with ten Matthayom 2 students in the 2025 academic year. The research instruments consisted of 1) three phenomenon-based learning unit plans for the Science Project subject, 2) a critical thinking ability test, and 3) an environmental literacy test. The data were analyzed using percentages and arithmetic means. The research results revealed that: 1) Three learning unit plans—Soil, Water, and Air—were designed to engage students in studying and solving real-world phenomena related to natural resources in their own context through inquiry-based learning and project work. The quality assessment by five experts indicated that all three units were rated at a high level. 2) Regarding learning outcomes, 70% of students achieved the criteria for critical thinking ability, with high scores in the components of problem definition and logical reasoning. In terms of environmental literacy, 60% of students achieved the criteria in environmental knowledge, while 80% demonstrated attitudes and behaviors toward the environment at high to very high levels.